PERBANDINGAN PERFORMANSI DATABASE MONGODB DAN MYSQL DALAM APLIKASI FILE MULTIMEDIA BERBASIS WEB - Mesri Silalahi (Universitas Putera Batam, 2018)
Database appeared and began to develop in line with the needs of processing and data storage to meet the information needs. Database is part of an important building block in an information system. In addition to a relational database (SQL), which stores structured datas in tables with defined schemes, there is a non-relational databases (NoSQL) with a dynamic scheme or unstructured. This study will compare the performance between NoSQL database (MongoDB) and SQL database (MySQL) for a web-based multimedia file storage application that stores files as BLOBs. Performance comparison is based on the speed of execution and the computer resources usage (CPU, memory, and virtual memory).